Matrix Metalloproteinases and Bladder Cancer: What is New?. (17th July 2012) - Rodriguez Faba, O.; Palou-Redorta, J.; Fernández-Gómez, J. M.; Algaba, F.; Eiró, N.; Villavicencio, H.; Vizoso, F. J.
Abstract : Urothelial bladder cancer represents a heterogeneous disease with divergent pathways of tumorigenesis. Tumor invasion and progression are a multifactorial process promoted by microenvironmental changes that include overexpression of matrix metalloproteinases (MMPs). Recent data clearly challenge the classic dogma that MMPs promote metastasis only by modulating the remodeling of extracellular matrix. Indeed, MMPs have also been attributed as an impact on tumor cell behavior in vivo as a consequence of their ability to cleave growth factors, cell surface receptors, cell adhesion molecules, and chemokines/cytokines. Levels of the different MMPs can be measured in several sample types, including tissue, blood (serum and plasma), and urine, and using different methodologies, such as immunohistochemistry, real-time PCR, western and northern blot analyses, enzyme-linked immunosorbent assay, and zymography. Several MMPs have been identified as having potential diagnostic or prognostic utility, whether alone or in combination with cytology. Although MMP inhibitors have shown limited efficacy, advances in the understanding of the complex physiologic and pathologic roles of MMPs might permit the development of new MMP-specific and tumor-specific therapies. In this paper we update the understanding of MMPs based on a systematic PubMed search encompassing papers published up to December 2011.